(untitled) (SCIENCE TIME JOURNAL, 2025)
this study examines the effectiveness of Task-Based Language Teaching (TBLT) in enhancing the reading competence of visually impaired learners. Through task-oriented reading activities adapted to auditory and tactile modalities, the research evaluates improvements in comprehension, fluency, and vocabulary. Findings reveal that TBLT fosters active learner engagement, promotes higher-order thinking skills, and provides inclusive strategies for reading instruction. The results offer practical implications for integrating TBLT into special education contexts.